Efficacy and safety of metformin for the treatment of gestational diabetes: a new approach to the problem - Anna I. Sazonova (Endocrinology Research Centre, 2016)
Historically, the following two methods were used to treat gestational diabetes mellitus: non-medical life-style interventions (diet and increased physical activity) and insulin treatment when other interventions were not effective. The possibility of alternative types of treatment such as oral anti-diabetic drugs has been the source of debate in recent years. Metformin is an oral anti-diabetic drug that reduces insulin resistance, which is common during gestation and is considered one of the main pathways of glucose metabolism alteration during pregnancy. The main concern is that metformin can cross the placenta and is found unchanged in foetal blood. This is the reason why oral anti-diabetic drugs are contraindicated during pregnancy in many countries, including Russia (according to the 2012 Russian recommendations for gestational diabetes treatment). In recent years, many studies investigating the safety and efficacy of metformin for maternal and foetal health have been published. We will review recent randomized clinical trials and discuss new international clinical recommendations (FIGO, 2015) and new opportunities for gestational diabetes mellitus treatment.